Efektivitas Penyampaian Informasi Keluhan Pelanggan Melalui Media Sosial PT PLN (Persero) - Mursib Mursib; Abdul Sadad (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
The purpose of conducting this research is to measure the level of effectiveness in conveying information about PT customer complaints. PLN (Persero) via social media and comparing it with the use of the PLN Mobile application. The use of social media is now important for state agencies to make it easier to provide services to the public, public services using social media as an intermediary according to Law of the Republic of Indonesia No. 11 of 2008 which explains about Electronic Information and Transactions, Article 4 Point (c) explained in detail that,